Pengaruh Terapi Musik Terhadap Penurunan Tingkat Kecemasan Anak Prasekolah Yang Mengalami Hospitalisasidi Paviliun Seruni Rsud Jombang - Ana Farida Ulfa; Kurniawati Kurniawati (coba, 2015)
Hospitalizationis a process by which aplannedor emergency reasons, so the children had to be hospitalized can cause children to experience anxiety. To over come anxiety management can be given psychotherapy, one of which is with music therapy. The purpose ofthis study was todetermine the effect of music therapy to decrease anxiety levels pre- school children who experienced hospitalization in Hospital Jombang Chrysan the mum Pavilion. This study uses the approach Quasy Experiment pretest-posttestdesign with control group. With a total sample of 14 children (2 groups) using purposive sampling technique. Data was collected through observation and then tabulated using data coding and tested using Mann Whitney and Wilcoxon with α = 0.05 significance level. The results of the analysis wilcoxon obtained p valueof 0.015, p value<α (0.015 <0.05) and Mann- Whitney obtained p valueof 0.007, p value<α (0.007<0.05). So there is the effect of music therapy on reducing anxiety levels preschoolers who experienced hospitalization in Hospital Jombang Chrysan the mum Pavilion. The conclusion that can bedrawn from this studyis the effect of music therapy on anxiety levels pre-school children who experienced hospitalization in Hospital Jombang Chrysan the mum Pavilion.